The Role of Capability, Regulation and the Use of Accounting Information Technology in Financial Management Performance - Suryanty, Leny; Saputra, Mulia; Abdullah, Syukriy (Universitas Syiah Kuala, 2021)
Objective This study aims to examine the effect of apparatus capability, the complete-ness of regulations, and the use of accounting information technology both simultaneous and partial on the financial management performance in SKPK Aceh Singkil, Indonesia.Design/methodology The population and unit analysis are the District Work Unit (SKPK) in Aceh Singkil, Indonesia. Respondents comprise of Budget Users (PA-SKPK), SKPK Financial Administration Officials (PPK-SKPK), and Finance Subdivision Heads of 46 SKPK. Documentation technique was utilized and Multiple Linear Regression Analysis was used to test the hypotheses.Results The results showed that apparatus capability, the completeness of regulations, and the use of accounting information technology simultaneous and partial affected the fi-nancial management performance in SKPK Aceh Singkil. This is a concern for SKPK to pay attention to these variables in improving management performance in Aceh Singkil Regency